SEZARY SYNDROM-CASE REPORT - Mitrova Telenta, Julija; Ahtarova, Biljana (SHMSHM - AAMD, 2021)
Sezary syndrome is a leukemic variant of primary CTCL (cutaneous T cell lymphoma) manifested with clinical triade consisting of erythroderma, peripheral lymphadenopathy and atypical mononuclear cells(Sezary cells).[8] We present a case of 45 years old female, with non-specific primary skin lesions which fastly progressed in erythrodermia. Skin biopsy, immunohistochemical investigations, biopsy from bone marrow and detectable Sezary cells>5% in periphery blood were inclusive for cutaneous limphoproliferative disease (Sezary syndrome). Lymph node punction showed atypical lymphocytes. RTG pulmo and ultrasound of abdomen without abnormalities. CHOP therapy was started. We present a case with Sezary syndrome, clinically classified T4N2M0 (stage IV A).
Keywords: primary cutaneous T cell lymphomas; Sezary syndrome; Sezary cells; CHOP therapy